"I'm Really Confident I Can Find the Exact IKEA Pillow": A Qualitative Look at the Search Self-Efficacy of Graduating MLIS Students. Issue 2 (3rd April 2017) - Hebert, Andrea; Duet, Jodi
Abstract: There is limited qualitative research on the information-seeking self-efficacy (SE) of library and information science (LIS) graduate students. This study examines graduating LIS students' experiences with information seeking, including experiences in the LIS program that led to increased levels of information-seeking SE and specific recollections of moments when SE increased. Many students identified similar factors as key to developing SE, including education-related assignments, library work experience, LIS internships, and specific LIS coursework. Because of the small sample size, further research would help to identify additional factors that promote LIS students' information-seeking SE.